Artificial intelligence - Mueller, John, 1958-; Massaron, Luca; Diamond, Stephanie (--For dummies., 2025)
Dive into the intelligence that powers artificial intelligence Artificial intelligence is swiftly moving from a sci-fi future to a modern reality. This edition of Artificial Intelligence For Dummies keeps pace with the lighting-fast expansion of AI tools that are overhauling every corner of reality.